Functions of connexin 46 in lens and solid tumors during hypoxia - Molina, Samuel A. (Kansas State University, 2012)
Eukaryotic cells possess a unique way to communicate with each other by passing metabolites and small molecules through protein pores that connect adjacent cells. Although there are many types and families of protein pores, connexins comprise a unique family. Six connexin monomers assemble into a hemichannel, which is transported to the cell membrane. An opposing cell membrane containing compatible connexin hemichannels is located and connected, forming an intercellular dodecameric protein complex. This results in a protein channel that connects two separate cytoplasmic compartments to each other. This type of channel is known as a gap junction. Connexin expression and function is commonly tissue specific. Of the 21 known human connexins, less than half are currently well characterized. Three connexins are expressed in the lens, connexin 43 (Cx43), 46 (Cx46), and 50 (Cx50). Of these three, Cx46 and Cx50 both have major functions in the mature lens. Cx46 functions as a major gap junction channel, which maintains mature lens homeostasis, while Cx50 possesses growth control properties in the lens. Cx46 expression is modulated in breast and bone tumors, and during ischemia. It is hypothesized that Cx46 provides resistance to hypoxia mediated cell death by prolonging survival. In this study, Cx46 expression was detected in human Y79 retinoblastoma cells. Decreasing the expression of Cx46 in nude mice carrying Y79 xenografts slowed early stage tumor growth. Y79 cells in culture survive for over 72 hours in 1% oxygen in vitro. C46 was upregulated in cultured lens cells when grown under hypoxia. Human lens epithelial cells, rabbit N/N1003A lens cells, and Y79 cells proliferated in 1% oxygen until Cx46 expression was depleted by use of siRNA. Protection from hypoxia-induced cell death was provided by transfection with the C-terminus of Cx46. We further determined that the promoter activity of Cx46 was increased in 1% oxygen. These results indicate that Cx46 would increase in response to hypoxia and suggest a role for Cx46 in protection from hypoxia. The studies demonstrate a novel function for Cx46 in cell survival during hypoxia.
Keywords: Gap Junction; Connexin; GJA3 Cx46; Hypoxic tumor; Lens; Biochemistry (0487); Biology, Animal Physiology (0433); Molecular Biology (0307)